The Earliest Occupation at Tel Bet Yerah. (20th October 2013) - Greenberg, Raphael; Rotem, Yael; Paz, Sarit
Abstract : The 2007 sounding in the northern part of Tel Bet Yerah yielded a stratigraphic sequence spanning the initial sequence of occupation on the mound, from EB IA to EB II. A robust ceramic assemblage, supported by radiocarbon dates, highlights the earliest part of the sequence. Comprising highly localized industries (including a little-known painted tradition) as well as regional ones (including Gray Burnished Ware), the Tel Bet Yerah assemblage provides a yardstick for ceramic evolution in the northern Jordan Valley between the end of the Chalcolithic and the mature EB I, offering a definition of two ceramic phases within an extended EB IA.